THE PHYSICIAN’S AND PATIENT’S PERCEPTION REGARDING THE INFLUENCE OF HEALTH INFORMATION ON THE WEB DURING CLINICAL CONSULTATIONS AT THE ANÁPOLIS CENTRAL UNIVERSITY OUTPATIENT CLINIC - da Conceià§ão , Eduarda Almeida Dutra; Lauck, Ana Júlia Martins; Malheiros, Amanda; Folgosi, Fernanda; Marques, Joaquim Pedro Figueira; Reis, Júlia Faria; Silva, Constanza Thaise Xavier (CIPEEX, 2022)
THE ADVENT OF THE INTERNET BROUGHT WITH IT AN EXPONENTIAL INCREASE IN THE ABILITY TO ACCESS INFORMATION IN AN EGALITARIAN MANNER, IN WHICH WHAT ONCE REQUIRED RESEARCH THROUGH SEVERAL BOOKS AND A LONG PERIOD OF DEDICATION, CAN NOW BE FOUND EASILY WITH A FEW CLICKS. WITH THIS, SEVERAL INTERPERSONAL RELATIONSHIPS HAVE UNDERGONE MAJOR CHANGES TO ADAPT TO THE NEW INFORMATION AGE, ESPECIALLY THE DOCTOR-PATIENT RELATIONSHIP. THE PRESENT STUDY AIMED TO DESCRIBE THE PERCEPTION OF THE PHYSICIAN AND PATIENT EXPERT AND THE MAIN INFLUENCES EXERTED BY THE USE OF THE INTERNET IN CLINICAL CONSULTATIONS. THIS IS AN OBSERVATIONAL, DESCRIPTIVE AND CROSS-SECTIONAL STUDY, OF A QUANTITATIVE NATURE, HAVING AS POPULATION THE PATIENTS AND THE DOCTORS OF THE CENTRAL UNIVERSITY OUTPATIENT CLINIC AND MAKING USE OF A SPECIFIC QUESTIONNAIRE CONTAINING OBJECTIVE QUESTIONS REGARDING THE USE OF THE INTERNET. ACCORDING TO THE DATA OBTAINED IN THE QUESTIONNAIRE, THE POPULATION WAS MADE UP OF 109 PATIENTS AT THE CENTRAL UNIVERSITY OUTPATIENT CLINIC OF ANÁPOLIS/GO. A PREDOMINANCE WAS OBSERVED IN THE FEMALE GENDER (80.7%); IN THE 40 TO 59 AGE BRACKET (47.7%); HIGH SCHOOL EDUCATION WITH 42.2%. 28.4% OF THE INTERVIEWEES SEARCH THE INTERNET AT LEAST ONCE DURING THE PAST WEEK; 34.9% SURF THE WEB FOR LESS THAN 2 HOURS A DAY; 66.1% HAVE BEEN USING THE INTERNET FOR MORE THAN 7 YEARS; 75.2% OF THE PATIENTS SEARCH THE WEB FOR INFORMATION SPECIFICALLY ABOUT MEDICINES; 73.4% HAVE NEVER BOUGHT THROUGH THE ONLINE PHARMACY; 36.7% DISAGREE THAT THEY FEEL SAFER AND MORE CONFIDENT WHEN THEY SEARCH FOR INFORMATION ON THE INTERNET BEFORE A DOCTOR’S APPOINTMENT; 48.6% AGREE THAT THE INFORMATION ON THE INTERNET NEEDS TO BE IMPROVED. ACCORDING TO THE PARTIAL DATA OBTAINED FROM THE QUESTIONNAIRES FOR THE DOCTORS, THE POPULATION CONSISTED OF 18 DOCTORS AT THE CENTRAL UNIVERSITY OUTPATIENT CLINIC OF ANÁPOLIS - GO. IT WAS OBSERVED A PREDOMINANCE OF MALES (77.8%) AND IN THE AGE GROUP OF 41 TO 50 YEARS. 94.4% OF THE DOCTORS STATED THAT THEY RECEIVE MANY PATIENTS WHO HAVE ALREADY SEARCHED THE INTERNET, WITH 83.3% STATING IT WAS VERY OFTEN. 44.4% SAID THEY DID NOT KNOW THE SOURCES BROUGHT BY THE PATIENTS, AND THE SAME PERCENTAGE SAID THEY DID. A LARGE PART OF THE INTERVIEWEES, ABOUT 77.8%, DO NOT TRUST THE INFORMATION BROUGHT BY PATIENTS FROM THE INTERNET; 56.6% DECLARED THEY HAVE NEVER NEEDED TO DISCUSS SOME INFORMATION BROUGHT ONLINE BY A PATIENT WITH ANOTHER PROFESSIONAL COLLEAGUE; 66.7% OFFER SOME KIND OF ONLINE SUPPORT FOR PATIENTS. IN VIEW OF THIS, WE CAN PROVE THAT THE INFORMED PATIENT HAS A CERTAIN POSITIVE SIDE AND ANOTHER NEGATIVE SIDE IN CLINICAL CONSULTATIONS, AND THE PHYSICIAN’S FUNCTION BECOMES EVEN MORE NECESSARY, CONSIDERING THAT DATA EVIDENCED IN THE LITERATURE, THE OBJECTIVE HAS BECOME MUCH MORE THAN JUST MAKING THE DIAGNOSIS AND TREATING DISEASES, AS IT SHOULD ALSO DIRECT THE PATIENT ABOUT ALL THE INFORMATION THAT HE/SHE CAN ACQUIRE IN RELIABLE SITES.